Electronically Tunable Impedance-Matching Networks for Intelligent RF Power Amplifiers - Liang Li; Taijun Liu; Yan Ye; Xiaojun Luo; Gang Cao; Xiaofeng Guo; Ming Hui (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper presents the simulation and optimization design of the electronically tunable impedance-matching networks for intelligent RF power amplifiers in a cognitive radio system. Reconfigurable elements, such as varactors and RF switches are utilized to achieve the dynamic impedance matching both in the input and output matching circuit, providing coarse and fine tuning of the target impedances with low loss and excellent impedance coverage from 500MHz to 800MHz. The topology of varactor model is illustrated to ensure the precision of simulation. In addition, high-precision bias voltage controlling system is designed to improve the nonlinear problem caused by the varactor. The simulation results demonstrate the excellent performance of the tunable networks, satisfying the requirement of the cognitive radio systems. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3514